Ukrainian liberation movement in 1940-1950 : institutionalization of researches (chosen aspects) - Ukhach, Vasyl (Actual problems of law (Aktual’ni problemi pravoznavstva), 2019)
The institutionalization processes of subjects researches of the Ukrainian liberation movement in the period of 1940–1950-ies in the context of the state policy of comorbidity and in particular the Ukrainian Institute of National Memory (created in 2006) are analyzed.